THE STUDY OF HUMORAL FACTORS OF ADAPTIVE IMMUNITY IN PATIENTS WITH NON-HODGKIN’S LYMPHOMAS - Tillyashaykhov M. N.; Abdiganiyeva S. R.; Abdurakhmonov D. A.; Tuidzhanova H. Kh.; Isroilova F. Kh.; Alimova S. S. (Science Review, 2019)
It is known that humoral factors of immunity play an important function of mediators in the cascade development of the immune response and can determine the effectiveness of the final, effector reactions of cellular immunity in the inactivation and elimination of antigens. Serum concentrations of major immunoglobulins IgG, IgA, IgM in NHL were analyzed. The highest serum content of IgG and IgA was revealed in the groups of patients with virus carrier. It has been established that one of the most important humoral markers of immunity is the circulating immune complexes (CIC). It has been established that one of the most important biological functions of immunoglobulins is antigen binding and the formation of CIC. A high level of CIC in NHL may be due not only to the activation of the immune response, but also to the suppression of the mechanisms of their elimination. Therefore, based on the results obtained, with NHL there is a pronounced imbalance of humoral immunity. CIC of large and small sizes are also increased, however, the highest increase in CIC was observed in groups of patients before chemotherapy with virus-bearing. An increase in the main immunoglobulins indicates the presence of humoral imbalance, and an increase in the CIC indicates the presence of intoxication of the body either due to the decay of the tumor cells themselves and infected cells, which almost always indicates the progression of the pathological process.